2016
DOI: 10.1121/1.4945588
|View full text |Cite
|
Sign up to set email alerts
|

Binaural hearing in children using Gaussian enveloped and transposed tones

Abstract: Children who use bilateral cochlear implants (BiCIs) show significantly poorer sound localization skills than their normal hearing (NH) peers. This difference has been attributed, in part, to the fact that cochlear implants (CIs) do not faithfully transmit interaural time differences (ITDs) and interaural level differences (ILDs), which are known to be important cues for sound localization. Interestingly, little is known about binaural sensitivity in NH children, in particular, with stimuli that constrain acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 44 publications
(51 reference statements)
5
24
0
Order By: Relevance
“…This approach shares some characteristics with a previous study that compared ILD lateralization ranges between NH and BiCI adults (Stakhovskaya and Goupell, 2017). For the current study, the DR for NH subjects was estimated to be 65 dB sound pressure level (SPL) based on the loudness growth function in NH adults for a 4-kHz tone (Allen et al, 1990), which was the carrier frequency for the pulse train presented to NH children in Ehlers et al (2016). Research has shown that children and adults show similar loudness growth functions (Serpanos and Gravel, 2000).…”
Section: B Analysismentioning
confidence: 96%
See 4 more Smart Citations
“…This approach shares some characteristics with a previous study that compared ILD lateralization ranges between NH and BiCI adults (Stakhovskaya and Goupell, 2017). For the current study, the DR for NH subjects was estimated to be 65 dB sound pressure level (SPL) based on the loudness growth function in NH adults for a 4-kHz tone (Allen et al, 1990), which was the carrier frequency for the pulse train presented to NH children in Ehlers et al (2016). Research has shown that children and adults show similar loudness growth functions (Serpanos and Gravel, 2000).…”
Section: B Analysismentioning
confidence: 96%
“…One of the questions that arises regarding binaural sensitivity in children with BiCIs is whether they perform similarly to or significantly worse than their peers with NH. Data from the current study were compared to NH children tested on the same task (Ehlers et al, 2016). It is worth noting that there is currently no accepted way to directly compare electric CUs to acoustic decibels (dB).…”
Section: B Analysismentioning
confidence: 99%
See 3 more Smart Citations